Review of the ecology and behaviour of Aedes aegypti and Aedes albopictus in Western Africa and implications for vector control - Egid, Beatrice R.; Coulibaly, Mamadou; Dadzie, Samuel Kweku; Kamgang, Basile; McCall, Philip J.; Sedda, Luigi; Toe, Kobié Hyacinthe; Wilson, Anne L. (Current research in parasitology & vector-borne diseases, 2022)
Western Africa is vulnerable to arboviral disease transmission, having recently experienced major outbreaks of chikungunya, dengue, yellow fever and Zika. However, there have been relatively few studies on the natural history of the two major human arbovirus vectors in this region, Aedes aegypti and Ae. albopictus, potentially limiting the implementation of effective vector control. We systematically searched for and reviewed relevant studies on the behaviour and ecology of Ae. aegypti and Ae. albopictus in Western Africa, published over the last 40 years. We identified 73 relevant studies, over half of which were conducted in Nigeria, Senegal, or Côte dʼIvoire. Most studies investigated the ecology of Ae. aegypti and Ae. albopictus, exploring the impact of seasonality and land cover on mosquito populations and identifying aquatic habitats. This review highlights the adaptation of Ae. albopictus to urban environments and its invasive potential, and the year-round maintenance of Ae. aegypti populations in water storage containers. However, important gaps were identified in the literature on the behaviour of both species, particularly Ae. albopictus. In Western Africa, Ae. aegypti and Ae. albopictus appear to be mainly anthropophilic and to bite predominantly during the day, but further research is needed to confirm this to inform planning of effective vector control strategies. We discuss the public health implications of these findings and comment on the suitability of existing and novel options for control in Western Africa. [Display omitted] •A comprehensive review on the behaviour and ecology of Aedes aegypti and Ae. albopictus in Western Africa.•Provides an update on insecticide resistance, indicating emerging resistance to organophosphates in Ae. aegypti.•Assesses suitability of existing and novel tools for controlling Ae. aegypti and Ae. albopictus in the region.•Highlights future directions for research, e.g. randomised controlled trials of tools with epidemiological outcomes.•Ae. aegypti and Ae. albopictus appear to be predominantly anthropophilic in Western Africa.